NiVCe-Layered Double Hydroxide as Multifunctional Nanomaterials for Energy and Sensor Applications - Gonçalves, Josué M.; Lima, Irlan S.; Azeredo, Nathália F. B.; Rocha, Diego P.; de Siervo, Abner; Angnes, Lúcio (Frontiers in Materials, 2021)
Multifunctional nanomaterials have been attracting increasing attention as solutions to the existing challenges in energy systems and sensing technologies. In this regards, multifunctional NiVCe-layered double hydroxide (NiVCe-LDH) nanoparticles were synthesized by modified sol-gel method. The analysis of this material demonstrated excellent potential for its utilization as electrode materials for hybrid supercapacitor, oxygen evolution reaction (OER) and sensor applications. The NiVCe-LDH nanoparticles delivered a specific charge of 740 C g-1 at 10 A g-1 and decent rate performance (charge retention of 68.7% at 100 A g−1), showing excellent prospects as electrode material for hybrid energy storage devices. In addition, NiVCe-LDH nanoparticles have also been successfully applied as proof-of-concept for OER, as confirmed by their low Tafel slope of 47 mV dec−1. Finally, trimetallic NiVCe-LDH-based screen-printed electrodes were developed for the sensing of hydrogen peroxide directly in a real complex mouthwash sample, achieving a satisfactory recovery value around 98% employing a fast and simple BIA procedure. These results allow us to predict the great potential of this trimetallic hydroxide for building electrochemical sensors with good perspectives as electroactive material for OER processes and energy storage technologies.